Biological control agents potential and molecular identification of endophytic Trichoderma isolates originated from oil palm tissue against Ganoderma boninense Pat. - Fifi Puspita; Titania T. Nugroho; Rachmad Saputra (Jurnal Ilmiah Pertanian, 2022)
This research aimed to determine the potential of endophytic Trichoderma sp originated from oil palm plant tissue as a biological control agent and its molecular identification. The potency assay was carried out using a completely randomized design consisting of three isolates of Trichoderma sp. from different plant tissues (TR01 from root tissue, TS01 from stem tissue, and TM01 from midrib tissue) with inhibitory ability parameters. The inhibition of the growth of G. boninense was performed at the concentration of 15% and 20%, and the molecular identification of Trichoderma sp. endophyte isolates was analyzed using BLAST software. The results showed that Trichoderma sp. TM01 isolate had larger inhibitory than the other isolates on days 3 and 4 by 60% and 68%. TM01 isolate also showed inhibition to the growth of the G. boninense at 15% and 20%, with the percentage of inhibition reaching 71.79% and 82.05%. Based on phylogenetic analysis, the three endophytic isolates of Trichoderma sp. were closely related to Trichoderma virens.